Viscosity Approximation Methods for Two Accretive Operators in Banach Spaces - Jun-Min Chen; Tie-Gang Fan (Abstract and Applied Analysis)
We introduced a viscosity iterative scheme for approximating the common zero of two accretive operators in a strictly convex Banach space which has a uniformly Gâteaux differentiable norm. Some strong convergence theorems are proved, which improve and extend the results of Ceng et al. (2009) and some others.